2011
DOI: 10.1007/s11816-011-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of trehalose increases soluble sugar contents in rice plants conferring tolerance to drought and salt stress

Abstract: Trehalose is a nonreducing sugar composed of two glucose units linked in an a,a-1,1-glycosidic linkage. Present in a wide variety of organisms, this sugar may serve as a source of energy and carbon and as a protective molecule against abiotic stresses. In this study, trehaloseproducing transgenic rice plants (Oryza sativa) expressing a bifunctional fusion enzyme TPSP (Ubi1:TPSP) were utilized to dissect the enigmatic role of trehalose in conferring stress tolerance to plants. Grown under normal conditions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…Trehalose is a well-studied metabolite associated with abiotic stress and the subject of various metabolic engineering efforts to enhance drought tolerance in plants. Overexpression of genes involved in trehalose metabolism increased drought tolerance in rice [41] and tomato [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Trehalose is a well-studied metabolite associated with abiotic stress and the subject of various metabolic engineering efforts to enhance drought tolerance in plants. Overexpression of genes involved in trehalose metabolism increased drought tolerance in rice [41] and tomato [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Trehalose and trehalose biosynthesis are important contributors to several physiological processes, including protection against stressors, not only in plants but also in animals, yeasts and bacteria (Jang et al 2003;Redillas et al 2012). Different approaches have been used to address and understand this pathway, such as overexpressing endogenous and exogenous genes encoding enzymes responsible for biosynthesis and hydrolysis of trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells degradation of trehalose is facilitated by the trehalase enzyme, which also contributes to the stability of this molecule and inhibits trehalose over-accumulation (Goddijn & Van Dun 1999). To date, several functional roles, such as osmoprotection, desiccation tolerance, storage energy (carbon) source, thermotolerance, regulation of growth and development and sugar signalling, have been attributed to trehalose and trehalose metabolism (Jang et al 2003;Veyres et al 2008;Redillas et al 2012;O'Hara et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose has also been reported to act as a free radical scavenger, thus helping the plant to reduce the cellular damages induced by stress-induced reactive oxygen species [63,64]. Besides its protective functions, trehalose may also act as an elicitor of genes involved in abiotic stress response [64], and it was shown to confer a high level of salt tolerance in rice, primarily through causing an increase in the synthesis of other soluble sugars [67]. It is noteworthy that Pace et al [44] recently reported that the level of soluble sugars in rapeseed correlated with tolerance of salinity stress.…”
Section: Discussionmentioning
confidence: 99%